Wage policies of a Russian firm and the financial crisis of 1998: Evidence from personnel data - 1997 to 2002 - Thomas Dohmen; Hartmut Lehmann; Mark E. Schaffer (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
We use a rich personnel data set from a Russian firm for the years 1997 to 2002 to analyze how the financial crisis in 1998 and the resulting change in external labor market conditions affect the wages and the welfare of workers inside a firm. We provide evidence that large shocks to external conditions affect the firm's personnel policies, and show that the burden of the shock is not evenly spread across the workforce. The firm takes advantage of a high-inflationary environment and of a fall in workers' outside options after the financial crisis and cuts real wages. Earnings are curbed most for those who earned the highest rents, resulting in a strong compression of real wages. The fact that real wages and real compensation levels never recovered to pre-crisis levels even though the firm's financial situation was better in 2002 than before the crisis and the differential treatment of employee groups within the firm can be taken as evidence that market forces strongly influence the wage policies of our firm.
Keywords: 330; Lohnniveau; Vergütungssystem; Interner Arbeitsmarkt; Finanzkrise; Russland